Authenticity: Shedding light on the branding context - Rosado-Pinto, F.; Loureiro, S. M. C. (EuroMed Journal of Business, 2024)
Purpose The purpose of this paper is to systematically review authenticity in the branding context and suggest avenues for future research. Design/methodology/approach This study applies a systematic literature review process and analyzes a total of 171 articles published from 1988 to 2021 and three items that are books or book chapters. Findings Brand authenticity has several definitions and dimensions. Although some common ground can be found among researchers, the study of authenticity is very fragmented. Even so, brand authenticity is often associated with a brand being genuine, real, true to itself and its consumers, and with consistent behavior, reflecting its values. A growing number of studies about the topic have been published, most of them empirical, applied in different industries and different geographical contexts. The authors also present several constructs associated with the topic (antecedents and consequences). Finally, this study shows paths for scholars to build on. Research limitations/implications The main limitations are associated with the inherent subjectivity related to the inclusion and exclusion criteria defined to select articles for the analysis. Originality/value This systematic review maps the past, structures existing knowledge about authenticity in the branding context, and sheds light on what could be future research in this field.